Moderasi Beragama Dalam Ruang Digital : Studi Harmonisasi Moderasi Beragama Di Perguruan Tinggi Keagamaan Islam Negeri - Aulia, Fira; Arifin, Fathul (Moderatio: Jurnal Moderasi Beragama, 2023)
Religious moderation refers to an intermediate grounding in one's approach to religious doctrines. This article was written as an introduction to the topic of the importance of moderation of religious behavior in digital media to encourage moderate and tolerant religious discourse. The digital world presents accessible religious narratives that can be used by relevant parties to resolve conflicts and challenge identity politics, characterized by weakening affiliation with religious organizations, the emergence of religious observers, declining individualism, and the transformation of pluralism. into tribalism. This research is qualitative research using an exploratory descriptive approach. Research results from harmonization of moderation in various domains in the digital space show its momentum. As an Islamic research laboratory, Islamic Religious Universities further modify content through digital media as a means of countering the spread of misinformation through social media. The generally accepted approach is the use of counter-narratives to dissolve the substantial, emotional family tree, i.e. moderate and tolerant.